Evaluation of The Effects of Psychotherapy on Anxiety Among Mothers of Children With Leukemia - NAZARI*, shiva; MORADI, Nahid; SADEGHI KOUPAEI, Mohammad Taghi (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Nazari Sh, Moradi N, Sadeghi Koupaei MT. Evaluation of The Effects of Psychotherapy on Anxiety Among Mothers of Children With Leukemia. Iran J Child Neurol. 2014 Winter; 8(1):52-57. Objective Children with leukemia and their families face a long period of medical treatment and uncertainty about the future. These families may suffer from short- and long-term emotional problems. The aim of the present study was to assess the effect of supportive psychotherapy on the anxiety of mothers whose children suffer from leukemia. Materials & Methods The current research were performed on mothers who had a child with leukemia hospitalized in Mofid Children’s Hospital, Tehran, Iran. They were randomly selected. The research method was a pseudo-experimental study with pretest/ posttest design. The pretest Kettles’ anxiety questionnaire was given to all the mothers and after seven sessions of supportive psychotherapy, the posttest was performed and the grades were compared. Results Ten mothers finished all seven therapeutic sessions. There was a statistically significant difference between the pretest and posttest mean scores, confirming the mothers’ reduced anxiety level. Conclusion Finding effective and newer approaches to improve the well-being of parents with a sick child is an important challenge of today’s medical researches. Based on our findings, it is possible to reduce the anxiety in mothers of children with leukemia through supportive psychiatric therapies. References Redaelli A, Laskin BL, Stephens JM, Botteman MF, Pashos CL. A systematic literature review of the clinical and epidemiological burden of acute lymphoblastic leukemia (ALL). Euro J Cancer Care 2005;14(1):53-62. Pourfathollah AA, Rakhshan M, Ahmadi M, Izadyar M. FAB Classification of childhood leukemia in Iran. Med J Islam Repub Iran 1988;4(2):263-4. Brown R, Madan-Swain A, Lambert R. Posttraumatic stress symptoms in adolescent survivors of childhood cancer and their mothers. J Trauma Stress 2003;16(4):309-18. Dolgin M, Phipps S, Fairclough D, Sahler OJ, Askins M, Noll R, et al. Trajectories of adjustment in mothers of children with newly diagnosed cancer: A natural history investigation. J Pediatr Psychol 2007;32(7):771-82. Patiño-Fernández AM, Pai A, Alderfer M, Hwang WT, Reilly A, Kazak A. Acute stress in parents of children newly diagnosed with cancer. Pediatr Blood Cancer 2008;50(2):289-92. Kazak A, Boeving A, Alderfer M, Hwang WT, Reilly A. Posttraumatic stress symptoms during treatment in parents of children with cancer. J clin oncol 2005;23(30):7405-10. Brown S, Yalom I. Interactional group psychotherapy with alcoholic patients. J Stud Alcohol 1977;38(3):426-456. Corraze J. An outline of General Psychopathology (Mental Diseases).Translated to Persian by Mansour M and Dadsetan P. Tehran: Roshd Publication; 2008. p.210-27. (Text in Persian) Sahler OJ, Fairclough D, Phipps S, Mulhern R, Dolgin M, Noll R, et al. Using problem-solving skills training to reduce negative affectivity in mothers of children with newly diagnosed cancer: Report of a multisite randomized trial. J Consult Clin Psychol 2005 Apr;73(2):272-83. Streisand R, Rodrique J, Houck C, Graham-Pole J, Berlant N. Brief Report: Parents of children undergoing bone marrow transplantation: Documenting stress and piloting a psychological intervention program. J Pediatr Psychol 2000;25(5):331-7. Wijnberg-Williams BJ, Kamps WA, Klip EC, Hoekstra-Weebers JE. Psychological distress and the impact of social support on fathers and mothers of pediatric cancer patients: Long-term prospective results. Journal J Pediatr Psychol 2006;31(8):785-92. Kazak AE, Alderfer MA, Streisand R, Simms S, Rourke MT, Barakat LP, et al. Treatment of posttraumatic stress symptoms in adolescent survivors of childhood cancer and their families: a randomized clinical trial. J Fam Psychol 2004;18(3):493-504. Young B, Dixon Woods M, Findly M, Heney D. Parenting in a crisis: conceptualizing of mothers of children with cancer. Soc Sci Med 2002;55(10):1835-47. Fisher HR. The need of parents with chronically sick children: a literature review. J Adv Nurs 2001;36(4):600-7. Stewart M, Davidson K, Meade D, Hirth A, Weld-Viscount P. Group support for couples coping with a cardiac condition. J Adv Nurs 2001;33(2):190-9. Kyngas H, Rissanen M. Support as a crucial predictor of good compliance of adolescents with a chronic disease. J Clin Nurs 2001;10:767-74.